Aerobic Oxidative Dehydrogenation of Amines Catalyzed by a Recoverable Ruthenium Catalyst under Mild Reaction Conditions. Issue 8 (15th January 2018) - Karimi, Babak; Yari, Omolbanin; Khorasani, Mojtaba; Vali, Hojatollah; Mansouri, Fariborz
Abstract: A highly active catalyst based on perruthenate ions supported inside the channels of periodic mesoporous organosilica with a bridged imidazolium ionic liquid framework (Ru@PMO‐IL) was developed. The material was found to be an efficient, durable, and recoverable catalyst for the oxidative dehydrogenation of various types of amines such as benzylic, aliphatic, and cyclic aliphatic amines under mild reaction conditions. The products were obtained in excellent yields with excellent selectivities. Abstract : Channel surfing : A highly stable perruthenate catalyst supported inside the channels of periodic mesoporous organosilica with a bridged imidazolium ionic liquid framework (Ru@PMO‐IL) is an efficient, durable, and recoverable catalyst for the oxidative dehydrogenation of various types of amines under mild reaction conditions. The products are obtained in excellent yields with excellent selectivities.